In vitro antiviral activities of enzymatic hydrolysates extracted frombyproducts of the Atlantic holothurian Cucumaria frondosa - Tripoteau, Ludovic; Bedoux, Gilles; Gagnon, Jacques; Bourgougnon, Nathalie (Process Biochemistry, 2015)
International audience tHerpes Simplex virus 1 (HSV-1), responsible for the common cold sore, can also lead to serious infectionsin immunocompromised people. Current antiviral chemotherapies face obstacles including the toxicityof therapeutic molecules, interference with normal cellular metabolism, genetic variability and the incur-able nature of latent infections. Therefore, the search for new treatments is a public health issue. Marineinvertebrates have held great potential for finding novel antiviral compounds. Little is known, about theantiviral activities of compounds isolated from holothurians. In New Brunswick, holothurian is fishedfor its edible bodywall and muscle, but its processing generates high amounts of byproducts. In vitroevaluation of the anti-HSV-1 activity by cell viability was performed on nine hydrolysates obtained byenzyme-assisted extraction and four solvent extractions from aquapharyngeal bulb and internal organsof Cucumaria frondosa at an MOI of 0.001 ID50/cells. After 72 h, four enzymatic hydrolysates from theaquapharyngeal bulb presented effective antiherpetic activities (EC50= 7.2–15.2 g/mL). After evalua-tion at a higher MOI (0.01 ID50/cells), the most efficient extract (Papain hydrolysate) was fractionatedto identify the active fraction. The fraction superior to 100 kDa showed the highest antiherpetic activity(EC50: 18.2 g/mL). In conclusion, upgrading byproducts of sea cucumber fisheries offers new sources ofbioactive molecules.